Physical and chemical investigation of water and sediment of the Keban Dam Lake, Turkey. Part 1: Iso-curves of radioactivity - Kulahci, F.; Do?ru, M. (My University, 2006)
The gross alpha- gross beta-activity, 137Cs and 90Sr in the water and sediment samples taken from the Keban Dam Lake, Uluova Region, was investigated in 2003 and 2004. We have found that in spring the concentration of 137Cs in the surface water and deep sediment changed between 0.001-0.01 Bq/l (0.4-2.5 Bq·kg-1) that of 90Sr between 0.0001-0.009 Bq/l (0.1-9 Bq·kg-1) and in autumn the values were 0.0001-0.009 Bq/l (0.4-8 Bq·kg-1) for 137Cs and 0.0002-0.005 Bq/l (0.6-4 Bq·kg-1) for 90Sr, respectively. The results were presented in form of iso-curves. © 2006 Akadémiai Kiadó.
Keywords: cesium 137; lake water; strontium 90; surface water; article; autumn; concentration (parameters); lake ecosystem; physical chemistry; quantitative analysis; radioactive pollution; sediment; spring; Turkey (republic); water analysis; water pollution